Utilization of Fine Motor Stimulation Media "Activity Book" for Stunting Toddlers - Zakiyya, Affi; Kurniatin, Lydia Febri (Journal of Health Sciences and Epidemiology, 2024)
Stunting conditions in toddlers affect physical performance and mental and intellectual functions to be disrupted. One of the efforts to avoid developmental delays in stunted toddlers requires an active role by the toddler's mother in providing stimulation. This study aimed to analyze the differences in toddlers' fine motor development before and after stimulation using activity book media. This study used a one-group pretest-postest design. The population in the study were toddlers who had been diagnosed with stunting in Sambas Regency, West Kalimantan, totaling 374 toddlers. Samples were taken using a cluster sampling technique in the Working Area of Puskesmas Tebas and Puskesmas Sekura, a total of 60 toddlers aged 24-36 months diagnosed with stunting. The research instrument was an "activity book" with 12 exercises. Hypothesis testing using the Wilcoxon Test after obtaining an abnormal data distribution in the data normality test. The findings of this study received the results p-value (0.000) <0.05. There were differences in the fine motor skills of stunted toddlers before and after being given stimulation using activity books.